Creative land : place and procreation on the Rai Coast of Papua New Guinea - Leach, James, 1969- (Berghahn Books, 2003)
"The book contains a new critique of the genealogical model of kinship, suggesting that this model prevents us from grasping the way generative relations, including those to land and place, constitute persons on the Rai Coast. Analytic attention is focused upon the life cycle, marriage, exchange and artistic production as the activities in which substantial connection is generated. The argument, made in relation to detailed ethnography, yields a fresh perspective on the connections people trace to each other."--Jacket